Non-equilibrium in soil hydraulic modelling - Vogel, Hans-Jörg; Weller, Ulrich; Ippisch, Olaf (Journal of hydrology, 2010)
A notorious problem in modelling water dynamics within the unsaturated zone is preferential flow and temporal non-equilibrium between water content and water potential. These phenomena originate from the ubiquitous spatial heterogeneity of soil hydraulic properties and substantially hampers the prediction of solute transport from the soil surface towards groundwater. The characteristic scale of these processes is the soil profile or ‘pedon scale’ where modelling of water dynamics is typically based on the well established Richards equation which has been augmented by various conceptual approaches to represent preferential flow phenomena. In this paper we investigate through numerical case studies hydraulic non-equilibrium during infiltration of water into relatively dry, heterogeneous soil profiles, which is the most prominent scenario where non-equilibrium conditions affect the overall dynamics of water and solutes...